2003
DOI: 10.1088/0963-0252/12/1/314
|View full text |Cite
|
Sign up to set email alerts
|

Supersonically expanding cascaded arc plasma properties: comparison of Ne, Ar and Xe

Abstract: Mathematical modelling was applied to study the dynamical and physical properties of the supersonically expanding rare gas plasma formed by a cascaded arc. Keeping constant the volume flow rate and the power input into the plasma, the Ne, Ar and Xe flows are compared. We demonstrate that the difference in mass flow rate affects the dynamic properties of plasma expansion. Modelling and experimental results show that the recombination heating of electrons is more significant in a gas that has a lower ionization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Even though the input power in the Ar plasma is lower than that in the He plasma, it is evident that both n e and T e are significantly higher in the Ar plasma than in the He plasma. The results are comparable to those obtained in the work of Selezneva et al, which explored the cascaded arc plasma characteristics in Ne, Ar, and Xe gases using mathematical modeling [23]. It was also found that both n e and T e in Xe plasma are higher than n e and T e in Ar plasma, whereas n e and T e in Ar plasma are higher than n e and T e in Ne plasma.…”
Section: Comparison Of Ne and Te Between He And Ar Plasmasupporting
confidence: 87%
See 1 more Smart Citation
“…Even though the input power in the Ar plasma is lower than that in the He plasma, it is evident that both n e and T e are significantly higher in the Ar plasma than in the He plasma. The results are comparable to those obtained in the work of Selezneva et al, which explored the cascaded arc plasma characteristics in Ne, Ar, and Xe gases using mathematical modeling [23]. It was also found that both n e and T e in Xe plasma are higher than n e and T e in Ar plasma, whereas n e and T e in Ar plasma are higher than n e and T e in Ne plasma.…”
Section: Comparison Of Ne and Te Between He And Ar Plasmasupporting
confidence: 87%
“…As shown in figure 5(a), the n e in cascaded arc Ar plasma is much higher than that in He plasma so that the threebody recombination can more effectively heat the electrons in Ar plasma. In fact, in Selezneva et al [23], it is also found that the electron gas is heated more effectively by recombination in Xe plasma than in Ar plasma, and the same is true for Ar and Ne. Therefore, the three-body recombination reaction in He plasma produces less energy for the electrons than it does in Ar plasma.…”
Section: Comparison Of Ne and Te Between He And Ar Plasmamentioning
confidence: 88%
“…We simulate the plasma flow using an axisymmetric model [26,31,35,36]. Since the ionization degree of the argon plasma is low (∼10%) [1,33], and the plasma becomes recombining in the downstream of the expanding plasma jet [26], the plasma flow dynamics can be modeled assuming a neutral hot gas expansion.…”
Section: Simulation Of the Plasma Expansionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] The particular application addressed here employs an Ar/ H 2 plasma, in the form of a dc arc jet, for methane activation and subsequent chemical vapor deposition ͑CVD͒ of polycrystalline diamond. [12][13][14][15][16][17][18][19][20] For completeness, we note that microwave-activated hydrocarbon/H 2 / Ar gas mixtures find even more widespread use for growing both CVD of single crystal, 21 microcrystalline, 22 and ͑at very low H 2 partial pressures͒ ultrananocrystalline diamond films.…”
Section: Introductionmentioning
confidence: 99%